Postoperative away from Noble's operation - Santos Dubra, Alfonso; Pollak Götzl, Erich W (Cirugía del Uruguay, 2020)
The long term post-operative course in the operation of Noble, as performed at the University Hospital of Montevideo, is discussed. 1) Of the 16 patients operated on, 12 have developed no new oclussions. 2) Of the 4 cases operated on for clinical oclussion, mechanical block has been observed only in l. 3) The course of total and partial Noble surgery is studied separately. 4) Attention is drawn to the pathological nature of the massive viscero-parietal adhesion and to the fact that it gives rise to intestinal symptoms, the condition being prevented by interposing the uninvolved greater omentum. 5) The salient features of an operative technique conducive to satisfactory results are discussed. 6) Adequate approach to occlusion from curling is dealt with.